第一个问题我想应该是这样的
ClearAll["Global`*"];
eq1 = f[x] + f[1/x] + 3 f[-x] == x;
eqs = eq1 /. {{x -> x}, {x -> -x}, {x -> 1/x}, {x -> -1/x}};
Solve[eqs, f[x] /. {{x -> x}, {x -> -x}, {x -> 1/x}, {x -> -1/x}}]
第二个问题
ClearAll["Global`*"];
eq1 = f[f[x]] == x^2 - 3 x + 4;
Simplify[Sequence @@ (eq1 /. {{x -> f[2]}, {x -> 2}})]
就求出了f[2]
但是f[x]的一般表达式是求不出来的, f[x]是按照

递推定义的
ClearAll["Global`*"];
eq1 = f[x] + f[1/x] + 3 f[-x] == x;
eqs = eq1 /. {{x -> x}, {x -> -x}, {x -> 1/x}, {x -> -1/x}};
Solve[eqs, f[x] /. {{x -> x}, {x -> -x}, {x -> 1/x}, {x -> -1/x}}]
第二个问题
ClearAll["Global`*"];
eq1 = f[f[x]] == x^2 - 3 x + 4;
Simplify[Sequence @@ (eq1 /. {{x -> f[2]}, {x -> 2}})]
就求出了f[2]
但是f[x]的一般表达式是求不出来的, f[x]是按照

递推定义的